Blockchain-powered traceability in the wine industry: Enhancing transparency and consumer trust - Manuela Cordeiro; Ferreira, J.; Luis Elvas; Vitor Basto-Fernandes (Blockchain: Research and Applications, 2026)
This study presents a blockchain-based traceability system designed to enhance transparency, combat counterfeiting, and strengthen consumer trust within the wine industry. The proposed solution employs a private MultiChain blockchain using a Proof of Authority (PoA) consensus mechanism to ensure data integrity, immutability, and accountability across the supply chain. Smart contracts are integrated to automate critical processes such as product registration, quality verification, and ownership transfers, while QR codes allow consumers to access the complete lifecycle history of each wine bottle. The system was developed and evaluated following the Design Science Research Methodology (DSRM) and tested in a real-world wine supply chain. Results demonstrate substantial improvements in traceability, regulatory compliance, and operational efficiency, including a 75% reduction in audit time and a measurable increase in consumer confidence. This research contributes a replicable and scalable framework for decentralized product identity management in agrifood supply chains, offering actionable insights for industry stakeholders and enriching the theoretical discourse on blockchain-enabled transparency in agriculture.